What is the Conservation Value of a Plant in a Botanic Garden? Using Indicators to Improve Management of Ex Situ Collections - Cibrian-Jaramillo, Angélica (2013)
Living botanic garden plant collections are a fundamental and underutilized worldwide resource for plant conservation. A common goal in managing a botanical living collection is to maintain the greatest biodiversity at the greatest economic and logistic efficiency. However to date there is no unified strategy for managing living plants within and among botanic gardens. We propose a strategy that combines three indicators of the management priority of a collection: information on species imperilment, genetic representation, and the operational costs associated to maintaining genetic representation. In combination or alone, these indicators can be used to assay effectiveness and efficiency of living collections, and to assign a numeric conservation value to an accession. We illustrate this approach using endangered palms that have been studied to varying degrees. Management decisions can be readily extended to other species based on our indicators. Thus, the conservation value of a species can be shared through existing databases with other botanic gardens and provide a list of recommendations toward a combined management strategy for living collections. Our approach is easily implemented and well suited for decision-making by gardens and organizations interested in plant conservation. © 2013 The New York Botanical Garden.